Determinants of Young Consumers' Activity on The Wine Tourism Market - Piotr KUŁYK; Mariola MICHAŁOWSKA; Andreea MUNTEAN; Martin STRAKA (Communications of International Proceedings, 2023)
Recently, tourism, including enotourism, has become an important factor in socio-economic development. It seems to be a promising area of action in terms of benefits not only for the city and its inhabitants, but also for global society. For the development of wine tourism, it is particularly important to observe consumer behavior, which changes due to changes in the environment. The main goal of this study is to assess the impact of wine tourism on the behavior of young consumers. The article contains the results of a survey conducted among respondents in the Lubuskie Voivodeship. The obtained results indicate that the majority of young consumers know and willingly visit Lubuskie vineyards, and they obtain information about them mainly from vineyard operators, wine sellers, family, friends and from their own experience. However, the main reasons for visiting vineyards included: participation in wine-related events and festivals, purchasing wine, as well as visiting vineyards and following thematic routes. Based on the research conducted, it was found that wine tourism undoubtedly helps improve the socio-economic situation. Building the region's identity and image through wine tourism as a tool for the region's development brings tangible benefits leading to its recognition and competitiveness. The results of this study provide valuable information for local authorities in shaping regional policy aimed at expanding wine tourism, in terms of assessing the existing potential of vineyards and further possibilities of their development.
Keywords: vineyards; Lubusz Voivodeship; young consumers; wine tourism